2011
DOI: 10.1002/eji.201141620
|View full text |Cite
|
Sign up to set email alerts
|

The binding activity of Mel‐18 at the Il17a promoter is regulated by the integrated signals of the TCR and polarizing cytokines

Abstract: We have previously shown that in differentiated T-helper (Th)1 and Th2 cells, polycomb group (PcG) proteins are associated differentially with the promoters of the signature cytokine genes. The correlation of the binding activity of PcG proteins with gene expression is unusual, since they are well known as epigenetic regulators that maintain transcriptional silencing. Here we show that in Th17 cells, the more phenotypically flexible Th lineage, the PcG proteins Mel-18 and less strikingly Ezh2 are associated di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 81 publications
(103 reference statements)
2
14
0
Order By: Relevance
“…15 The enrichment of Mel-18 targets was also important, given that Mel-18 has been observed to be a key component in Th17 cell programming. 16 …”
Section: Transcriptomics Distinguish Hyperacute and Breakthrough Acutmentioning
confidence: 99%
“…15 The enrichment of Mel-18 targets was also important, given that Mel-18 has been observed to be a key component in Th17 cell programming. 16 …”
Section: Transcriptomics Distinguish Hyperacute and Breakthrough Acutmentioning
confidence: 99%
“…(2,41) Several studies point to an important role of Ezh2 and H3K27me3 in multiple lineages of effector T cells. (14,17,20,25) Genome-wide mapping analysis revealed that repressive H3K27me3 marked genes associated with differentiation and maintenance of effector and memory T cells. (1,51) Most recently, we have demonstrated new and essential roles of Ezh2 in regulating inflammatory T cell responses in mice after allogeneic BMT.…”
Section: Introductionmentioning
confidence: 99%
“…However, whether genetic inactivation of Ezh2 leads to inappropriate differentiation of Th1 and Th2 has not been effectively tested. A recent study has shown that Ezh2 also positively correlated to the expression of IL17A and IL17F [90]. These studies pointed to a potential impact of Ezh2 and repressive H3K27me3 in multiple lineages of effector T cells.…”
Section: Function Of Histone Methyltransferases In Effector T Cellsmentioning
confidence: 91%
“…Some studies suggested that Ezh2 was correlated with Th1 and Th2 cell development [24,90,91]. Ezh2 bound to the IFNG promoter and proximal transcribed region both in Th1 and Th2 cells [91].…”
Section: Function Of Histone Methyltransferases In Effector T Cellsmentioning
confidence: 99%